2002
DOI: 10.1038/sj.bmt.1703715
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation as salvage therapy for high-risk patients with myeloma in relapse

Abstract: Summary:Patients with myeloma relapsing after tandem transplant have a poor survival and treatment options are limited. The role of additional salvage transplant procedures for these patients is unknown. To evaluate the benefit and identify prognostic factors, the outcome of 76 consecutive patients with recurrent myeloma after tandem transplant receiving salvage transplants (ST) was analyzed. Prior to ST, 23 patients (30%) had shown chemosensitive response to preceding salvage chemotherapy: two complete remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Finally, a randomized trial comparing early versus late ASCT demonstrated improved PFS for earlier transplantation (39 months vs. 13 months), while OS was not significantly different. Early ASCT was also associated with an improved quality of life and higher remission rates, thought to arise because of the better performance status of the patients with early ASCT who were also less heavily pretreated [60][61][62][63][64][65][66][67][68][69][70] and thus less likely to have multi-drug resistant disease. Future studies will need to more clearly define the benefit of 'upfront' ASCT versus deferring the procedure, as current data suggest that the median OS with early versus delayed ASCT may be similar, bearing in mind, of course, that with later-scheduled ASCT, patients may never actually get to transplant.…”
Section: Table III Novel Agent Combinations With Autologous Stem Celmentioning
confidence: 99%
“…Finally, a randomized trial comparing early versus late ASCT demonstrated improved PFS for earlier transplantation (39 months vs. 13 months), while OS was not significantly different. Early ASCT was also associated with an improved quality of life and higher remission rates, thought to arise because of the better performance status of the patients with early ASCT who were also less heavily pretreated [60][61][62][63][64][65][66][67][68][69][70] and thus less likely to have multi-drug resistant disease. Future studies will need to more clearly define the benefit of 'upfront' ASCT versus deferring the procedure, as current data suggest that the median OS with early versus delayed ASCT may be similar, bearing in mind, of course, that with later-scheduled ASCT, patients may never actually get to transplant.…”
Section: Table III Novel Agent Combinations With Autologous Stem Celmentioning
confidence: 99%
“…To our knowledge, here is no standard salvage treatment for patients who develop disease recurrence after an autograft. Treatments ranging from conventional agents to salvage autologous and allogeneic transplants have been used 5–11…”
mentioning
confidence: 99%
“…Also, some groups propose the transplantation of as many hematopoietic progenitor cells as possible leading to faster hematopoietic recovery and improved outcome [10]. Additionally, even after tandem transplantation, a third high-dose melphalan therapy can be of benefit in case of disease progression after a reasonable remission duration [25]. Therefore, a collection of progenitor cells in patients diagnosed with multiple myeloma should aim at enough cells for more than one transplant.…”
Section: Discussionmentioning
confidence: 98%